PENGARUH E-MONEY DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF DIKALANGAN MAHASISWA DALAM EKONOMI ISLAM (Studi Kasus Mahasiswa Ekonomi Islam Universitas Jambi) - Khairun Najwa; Nurida Isnaeni (CV SWA Anugrah, 2023)
This research aims to determine the influence of the use of electronic money and lifestyle on consumer behavior among students. And to find out the consumer consumer behavior that arises when using E-money among Jambi University Islamic Economics Study Program students. This research uses a quantitative approach with survey research methods. The population of this research is Islamic Economics students at Jambi University 2020, 2021, 2022, totaling 399 students with a sample size of 80 students. Sampling used purposive sampling technique. Data collection uses questionnaires and analysis uses simple linear regression analysis. The research results show that there is an influence of the use of E-Money and lifestyle on consumptive behavior, and the consumptive behavior of students that arises from using E-Money is not considering function/use, consuming goods excessively prioritizing desires over needs.